The bioelectrical basis and validity of gastrointestinal extracellular slow wave recordings. (28th June 2013) - Angeli, Timothy R.; Du, Peng; Paskaranandavadivel, Niranchan; Janssen, Patrick W.M.; Beyder, Arthur; Lentle, Roger G.; Bissett, Ian P.; Cheng, Leo K.; O'Grady, Gregory
Key points:   Extracellular recording techniques are commonly used to measure bioelectrical activity. However, the validity of gastrointestinal extracellular recordings has recently been challenged.   In this joint experimental and modelling study, slow waves were recorded during contractile inhibition, biphasic and monophasic slow wave potentials were recorded simultaneously, and the biophysical basis of extracellular potentials was modelled with comparison to experimental data.   The results showed that in vivo extracellular techniques reliably recorded slow waves in the absence of contractions, and potentials recorded using conventional serosal electrodes (biphasic) were concordant in phase and morphology with those recorded using suction electrodes (monophasic).   Modelling further demonstrated that the morphology of experimental recordings is consistent with the biophysics underlying slow wave depolarisation.   In total, these results demonstrate that gastrointestinal extracellular recordings are valid when performed and analysed correctly, reliably representing bioelectrical slow wave events. Motion suppression is not routinely required for in vivo extracellular studies. Abstract  Gastrointestinal extracellular recordings have been a core technique in motility research for a century. However, the bioelectrical basis of extracellular data has recently been challenged by claims that these techniques preferentially assay movement artifacts, cannot reproduce the underlying slow wave kinetics, and misrepresent the true slow wave frequency. These claims motivated this joint experimental–theoretical study, which aimed to define the sources and validity of extracellular potentials. In vivo extracellular recordings and video capture were performed in the porcine jejunum, before and after intra‐arterial nifedipine administration. Gastric extracellular recordings were recorded simultaneously using conventional serosal contact and suction electrodes, and biphasic and monophasic extracellular potentials were simulated in a biophysical model. Contractions were abolished by nifedipine, but extracellular slow waves persisted, with unchanged amplitude, downstroke rate, velocity, and downstroke width ( P > 0.10 for all), at reduced frequency (24% lower; P = 0.03). Simultaneous suction and conventional serosal extracellular recordings were identical in phase (frequency and activation–recovery interval), but varied in morphology (monophasic vs . biphasic; downstroke rate and amplitude: P < 0.0001). Simulations demonstrated the field contribution of current flow to extracellular potential and quantified the effects of localised depolarisation due to suction pressure on extracellular potential morphology. In sum, these results demonstrate that gastrointestinal extracellular slow wave recordings cannot be explained by motion artifacts, and are of a bioelectrical origin that is highly consistent with the underlying biophysics of slow wave propagation. Motion suppression is shown to be unnecessary as a routine control in in vivo extracellular studies, supporting the validity of the extant gastrointestinal extracellular literature.